Artificial insemination and the opinion of philosophers about it - AsadAlaah, Nada Sabah; AlHaideri, Ehsan Ali Abdul Ameer (Al-Adab Journal, 2023)
The research deals with the topic of insemination and incubation, and is considered one when external insemination is ideal (with children, and I am children). The process of artificial insemination does not raise any problems if it is carried out between spouses, but the problem is that it is performed on single women, and here the opinion of the philosophers and their position on this process is presented and their views are explained because the philosophers have a comprehensive, rational and logical view on the subject of artificial insemination and what progress has resulted in The great scholar in medicine and biology.